2013
DOI: 10.2147/ijn.s39031
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured magnesium has fewer detrimental effects on osteoblast function

Abstract: Efforts have been made recently to implement nanoscale surface features on magnesium, a biodegradable metal, to increase bone formation. Compared with normal magnesium, nanostructured magnesium has unique characteristics, including increased grain boundary properties, surface to volume ratio, surface roughness, and surface energy, which may influence the initial adsorption of proteins known to promote the function of osteoblasts (boneforming cells). Previous studies have shown that one way to increase nanosurf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…Accordingly, a neutralizing diet improves bone micro-architecture and bone mineral density [52]. It is therefore feasible that part of the effects of Mg on the skeleton is due to its capability to act as a buffer for the acid produced by the typical western diet [53]. …”
Section: Low Magnesium and Osteoporosis: Studies In Humansmentioning
confidence: 99%
“…Accordingly, a neutralizing diet improves bone micro-architecture and bone mineral density [52]. It is therefore feasible that part of the effects of Mg on the skeleton is due to its capability to act as a buffer for the acid produced by the typical western diet [53]. …”
Section: Low Magnesium and Osteoporosis: Studies In Humansmentioning
confidence: 99%
“…Hong et al ( 4 ) directly cultured a murine osteoblast-like cell line (MC3T3) on Mg-4 wt.% Zn-0.5 wt.% Zr (ZK40) alloy and found favorable cell viability and attachment. Weng et al ( 5 ) reported that nanostructured magnesium could influence the initial adsorption of proteins known to promote the function of osteoblasts. Furthermore, a clear stimulation of cell proliferation and an enhancement of the mitochondrial respiratory activity were observed when mouse osteoblasts (MC3T3-E1) were cultured with a fluoride surface-modified AZ31 magnesium alloy (AZ31HF), compared to bare-coated ones ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these intraporous nanofibers may augment the scaffold in two additional ways: these fibers may assist in the migration of cells throughout the scaffold and they may provide cells with additional surface area on which to lay down their own ECM. The second positive effect of providing additional surface area may be further expanded because osteoblasts are known to sense the underlying nanoscale features of their substrate and adjust their function accordingly [ 16 ]. Recently, Brown et al [ 17 ] described a scaffold system that brought together sintered poly(phosphazene) microspheres and synthetic ECM-mimetic nanofibers.…”
Section: Resultsmentioning
confidence: 99%